Heuristic Evaluation Based on Lifted Relaxed Planning Graphs - Ridder, Bram; Fox, Maria (Proceedings of the International Conference on Automated Planning and Scheduling, 2014)
In previous work we have shown that grounding, while used by most (if not all) modern state-of-the-art planners, is not necessary and is sometimes even undesirable. In this paper we extend this work and present a novel forward-chaining planner that does not require grounding and can solve problem instances that are too large for current planners to handle. We achieve this by exploiting equivalence relationships between objects whist constructing a lifted version of the relaxed planning graph (RPG) and extracting a relaxed plan. We compare our planner to FF and show that our approach consumes far less memory whist still being competitive. In addition we show that by not having to ground the domain we can solve much larger problem instances.